Fabrication of blood‐derived elastogenic vascular grafts using electrospun fibrinogen and polycaprolactone composite scaffolds for paediatric applications. (26th July 2020) - Woods, Ian; Black, Alexander; Molloy, Eleanor J.; Jockenhoevel, Stefan; Flanagan, Thomas C.
Abstract: The development of tissue‐engineered vascular grafts (TEVGs) for paediatric applications must consider unique factors associated with this patient cohort. Although the increased elastogenic potential of neonatal cells offers an opportunity to overcome the long‐standing challenge of in vitro elastogenesis, neonatal patients have a lower tolerance for autologous tissue harvest and require grafts that exhibit growth potential. The purpose of this study was to apply a multipronged strategy to promote elastogenesis in conjunction with umbilical cord‐derived materials in the production of a functional paediatric TEVG. An initial proof‐of‐concept study was performed to extract fibrinogen from human umbilical cord blood samples and, through electrospinning, to produce a nanofibrous fibrinogen scaffold. This scaffold was seeded with human umbilical artery‐derived smooth muscle cells (hUASMCs), and neotissue formation within the scaffold was examined using immunofluorescence microscopy. Subsequently, a polycaprolactone‐reinforced porcine blood‐derived fibrinogen scaffold (isolated using the same protocol as cord blood fibrinogen) was used to develop a rolled‐sheet graft that employed topographical and biochemical guidance cues to promote elastogenesis and cellular orientation. This approach resulted in a TEVG with robust mechanical properties and biomimetic arrangement of extracellular matrix (ECM) with rich expression of elastic fibre‐related proteins. The results of this study hold promise for further development of paediatric TEVGs and the exploration of the effects of scaffold microstructure and nanostructure on vascular cell function and ECM production.